Differentiation of stem cells into insulin‐producing cells under the influence of nanostructural polyoxometalates. Issue 3 (23rd September 2015) - Bâlici, Ştefana; Şuşman, Sergiu; Rusu, Dan; Nicula, Gheorghe Zsolt; Soriţău, Olga; Rusu, Mariana; Biris, Alexandru S.; Matei, Horea
Abstract: Two polyoxometalates (POMs) with W were synthesized by a two‐step, self‐assembling method. They were used for stimulation of mesenchymal stem cell differentiation into insulin‐producing cells. The nanocompounds (tris(vanadyl)‐substituted tungsto‐antimonate(III) anions [POM1] and tris‐butyltin‐21‐tungsto‐9‐antimonate(III) anions [POM2]) were characterized by analytical techniques, including ultraviolet‐visible, Fourier transform infrared, nuclear magnetic resonance spectroscopy, and transmission electron microscopy. We found that these polyoxotungstates, with 2–4 nm diameters, did not present toxic effects at the tested concentrations. In vitro, POM1 stimulated differentiation of a greater number of dithizone‐positive cells (also organized in clusters) than the second nanocompound (POM2). Based on our in vitro studies, we have concluded that both the POMs tested had significant biological activity acting as active stimuli for differentiation of stem cells into insulin‐producing cells. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Two nanostructural polyoxometalates with diameters of 2–4 nm were synthesized and characterized by electron microscopy and spectroscopy. It was found that both nanomaterials stimulate stem cell differentiation into insulin producing cells, without presenting toxic effects at the working concentrations.